PAVLA VOŠAHLÍKOVÁ, Rákoska v dílně lidskosti. Česká škola v 19. století očima účastníků, Praha 2016, Academia, 312 s., ISBN 978-80-200-2533-3 - Charvát, Šimon (Dějiny – teorie – kritika, 2016)
Book review